Untangling 'Familiness': A Literature Review and Directions for Future Research. (August 2013) - Weismeier-Sammer, Daniela; Frank, Hermann; von Schlippe, Arist
The influence of the family on business has been the subject of much debate, particularly with regard to the assumed familiness of family businesses. The term 'familiness' is at risk of becoming an umbrella concept and is often used haphazardly, lacking a solid theoretical background. This review provides a structured overview of the literature addressing the idea of familiness. Over the last 13 years, research on this key concept has grown continually, resulting in a broadening rather than a deepening of the concept of familiness. The results of the analysis of 33 manuscripts are presented and consolidated into three main categories: (1) theoretical perspectives; (2) the development and impact of familiness; and (3) empirical approaches. The analysis shows that existing research on familiness lacks the application of a universal theoretical lens. The authors counteract this shortfall by introducing new systems theory and presenting promising directions for further research, especially with regard to the development of a familiness typology.